Variation and in vitro splicing of group I introns in rRNA genes of Pneumocystis carinii. - Liu, Y (1993)
The sequences of the rRNA genes of Pneumocystis carinii from rat and human sources demonstrate three distinct genotypes based on the group I introns present in these genes. One rat isolate (Pc1) contains such introns in its 16S and 26S rRNA genes, while another rat isolate (Pc2) and a human isolate (Pc3) only contain an intron in the 26S rRNA gene. The four introns all catalyze their own excision from RNA transcripts, and this reaction is inhibited by the anti-pneumocystis drug pentamidine and its analogues. Although they differ in sequence, they are more similar to one another than to group I introns found in other eukaryotic microbes.